2011
DOI: 10.1634/theoncologist.2011-0169
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cigarette Smoking on Cancer Treatment–Related Side Effects

Abstract: After completing this course, the reader will be able to:1. Describe the influence of cigarette smoking on side effects during cancer treatment and following the end of cancer treatment.2. Identify areas in your practice in which smoking status can be assessed on a regular basis and devise a plan for disseminating cessation information and free cessation aids.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTBackground. Cigarette smoking has long been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 60 publications
6
88
0
1
Order By: Relevance
“…Continued smoking by tobacco dependent cancer patients is associated with greater risk of recurrence (Fleshner et al, 1999; Kenfield, Stampfer, Chan, & Giovannucci, 2011), reduced survival (Murin & Inciardi, 2001; Parsons, Daley, Begh, & Aveyard, 2010; Waggoner et al, 2006; Warren, Kasza, Reid, Cummings, & Marshall, 2012) and quality of life (Garces et al, 2004; Peppone et al, 2011); and an increased risk of peri-operative complications during treatment(Dresler, Bailey, Roper, Patterson, & Cooper, 1996; Moller, 2006; Theadom & Cropley, 2006; Warner, 2006). …”
mentioning
confidence: 99%
“…Continued smoking by tobacco dependent cancer patients is associated with greater risk of recurrence (Fleshner et al, 1999; Kenfield, Stampfer, Chan, & Giovannucci, 2011), reduced survival (Murin & Inciardi, 2001; Parsons, Daley, Begh, & Aveyard, 2010; Waggoner et al, 2006; Warren, Kasza, Reid, Cummings, & Marshall, 2012) and quality of life (Garces et al, 2004; Peppone et al, 2011); and an increased risk of peri-operative complications during treatment(Dresler, Bailey, Roper, Patterson, & Cooper, 1996; Moller, 2006; Theadom & Cropley, 2006; Warner, 2006). …”
mentioning
confidence: 99%
“…Smokers tended to be younger than non-smokers, which is consistent with another study that reported that patients who smoked during cancer radiotherapy tended to be younger than non-smokers. 19 We were unable to control for the potential confounding effects of other patient-related factors, such as alcohol use and buccal and dental hygiene status because this information was not collected. However, other studies have suggested that smokers have less-favourable baseline characteristics, such as socio-demographic characteristics (lower educational level, less familial support, poorer self-rated baseline health status), which increase their risk of developing treatment-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…In radiotherapy for prostate cancer smoking is associated with an increased risk of experiencing long-term bowel and anal-sphincter region related side effects 52 . Across cancer sites, non-smokers have been shown to suffer a significantly reduced burden of symptoms after radiotherapy or chemotherapy 53 . Thus, smoking cessation in radiotherapy patients should be encouraged by practitioners for all patients, not just those with an aetiological tobacco associated cancer, as smoking can significantly increase sideeffects 11 , reduce quality of life 9,10 and prognosis in these patients 12,13 .…”
Section: Required Knowledgementioning
confidence: 99%
“…Across cancer sites, non-smokers have been shown to suffer a significantly reduced burden of symptoms after radiotherapy or chemotherapy 53 . Thus, smoking cessation in radiotherapy patients should be encouraged by practitioners for all patients, not just those with an aetiological tobacco associated cancer, as smoking can significantly increase sideeffects 11 , reduce quality of life 9,10 and prognosis in these patients 12,13 . Informing therapeutic radiographers of the evidence and improving their knowledge in this area is likely to facilitate delivery of smoking cessation to these patients 41 .…”
Section: Required Knowledgementioning
confidence: 99%
See 1 more Smart Citation